2006
DOI: 10.1142/s0218271806009637
|View full text |Cite
|
Sign up to set email alerts
|

Supermassive Black Holes or Boson Stars? Hair Counting With Gravitational Wave Detectors

Abstract: The evidence for supermassive Kerr black holes in galactic centers is strong and growing, but only the detection of gravitational waves will convincingly rule out other possibilities to explain the observations. The Kerr spacetime is completely specified by the first two multipole moments: mass and angular momentum. This is usually referred to as the "no-hair theorem", but it is really a "two-hair" theorem. If general relativity is the correct theory of gravity, the most plausible alternative to a supermassive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 29 publications
(43 reference statements)
1
51
0
Order By: Relevance
“…They computed the dominant axial oscillation modes and found no instabilities. In analogy with previous studies of the oscillation modes of boson stars [29][30][31], they confirmed that the axial QNM spectrum of gravastars can be used to discern a gravastar from a BH. In the thin-shell limit, the axial QNM frequencies of Ref.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…They computed the dominant axial oscillation modes and found no instabilities. In analogy with previous studies of the oscillation modes of boson stars [29][30][31], they confirmed that the axial QNM spectrum of gravastars can be used to discern a gravastar from a BH. In the thin-shell limit, the axial QNM frequencies of Ref.…”
Section: Introductionsupporting
confidence: 82%
“…Building on Ryan's proposal, Kesden et al showed that the inspiral of a small compact object into a nonrotating boson star will emit a rather different gravitational waveform at the end of the evolution, when the small object falls into the central potential well of the boson star instead of disappearing into the event horizon of a BH [28]. Several authors have computed the QNM spectrum of boson stars, showing that it is remarkably different from the QNM spectrum of BHs and lending support to the feasibility of no-hair tests using QNM measurements [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore a measurement of the frequency and damping time of a QNM can be used to infer the mass and angular momentum of the BH with potentially high accuracy [9,79,10,11]. Since the whole QNM spectrum depends solely on M and a, the measurement of two or more QNM frequencies provides a stringent observational test of the no-hair theorem of general relativity [461,462,11,463]. The prospects for detecting the signature of BH oscillations in gravitational waves are the main topic of this section.…”
Section: Quasinormal Modes Of Astrophysical Black Holesmentioning
confidence: 99%
“…In conclusion, ringdown radiation can be used to distinguish BHs from exotic alternatives, such as boson stars [463] or gravastars [664]. Ringdown tests of the Kerr nature of astrophysical BHs are independent from (and complementary to) proposed tests using a multipolar mapping of the Kerr spacetime, as encoded in EMRI signals according to "Ryan's theorem" and its generalizations [665,666,667].…”
Section: Tests Of the No-hair Theoremmentioning
confidence: 99%
“…We remark that boson stars have been suggested as BH mimickers, and studies in this context, including of the comparative phenomenology, have been report in, e.g. [53][54][55][56][57][58][59][60][61][62][63][64].…”
Section: Introductionmentioning
confidence: 99%